Evaluating Complex Health Interventions With Randomized Controlled Trials: How Do We Improve the Use of Qualitative Methods?. (April 2019) - Mannell, Jenevieve; Davis, Katy
Qualitative methods are underutilized in health intervention evaluation, and overshadowed by the importance placed on randomized controlled trials (RCTs). This Commentary describes how innovative qualitative methods are being used as part of RCTs, drawing on articles included in a special issue of Qualitative Health Research on this topic. The articles' insights and a review of innovative qualitative methods described in trial protocols highlights a lack of attention to structural inequalities as a causal mechanism for understanding human behavior. We situate this gap within some well-known constraints of RCT methodologies, and a discussion of alternative RCT approaches that hold promise for bringing qualitative methods center stage in intervention evaluation, including adaptive designs, pragmatic trials, and realist RCTs. To address the power hierarchies of health evaluation research, however, we argue that a fundamental shift needs to take place away from a focus on RCTs and toward studies of health interventions.